Incidence of lumbarization and sacralization in normal and low backache patients A roentgenogram study (International Journal of Biomedical Research, 2014)
Background : In lumbosacral transitional zone number of vertebrae is variable and unreliability of anatomical landmark for identification of last lumbar vertebrae make the region interesting for research purpose. On the other hand its correlation with low backache makes it more clinically relevant than anatomically. Objective: To study the prevalence of lumbarization and sacralization of vertebrae in lumbosacral transitional zone in study population and in patients with low backache. Material and method : Radiographs of the entire spine of 100 patients were examined. 50 radiographs out of these were of patients with low backache and 50 radiographs of age and sex matched normal subjects, having problems other than low backache. Result: In the present study, it was observed that incidence of sacralization and lumbarization was 5% and of 10% respectively in the study population but this incidence was increased in low backache patients to 8% sacralization and 18% lumbarization. It was also perceived that around 22.2% female had lumbarization in comparisons to males (25%) in 31- 40 years of age group of low backache patients. Incidence of sacralization was also higher in male (i.e. 25%) in comparison to female (i.e. 11.7%). Conclusion: From these observations in the present study, it may be concluded that increase in incidence of lumbarization and sacralization may lead to increased chances of low backache and also higher incidence of lumbarization and sacralization in males perhaps make them more vulnerable to low backache.